Effects of Microbial Transglutaminase and Fermentation Type on Improvement of lysine Availability in Wheat Bread: A Response Surface Methodology - Mollakhalili Meybodi, Neda; Mortazavian, Amir Mohammad; Mirmoghtadaie, Leila; Hosseini, Seyede Marzieh; Yasini, Seyyed Ali; Azizi, Mohammad Hossein; Mousavi Nodoushan, Somayeh (Applied Food Biotechnology, 2019)
Background and objective: Lysine-glutamine crosslink formation catalyzed by microbial transglutaminase is supposed to affect improvement of lysine availability in wheat bread. Present study is done to investigate the effect of microbial transglutaminase and fermentation type in improvement of the lysine availability of wheat bread. Material and methods: Lysine-fortified wheat breads were formulated using response surface methodology with composite-face central design. Statistical models were used to predict the impact of defatted soy flour level (0-50% w w-1), microbial transglutaminase level (0-1.6% w w-1) and fermentation type (yeast or mixed fermentation based on sourdough). Further information was provided on the individual role of independent variables in nutritional and structural characteristics of optimized formulation and blank and control samples. Experiments were carried out in triplicate and the mean values were analyzed using one-way analysis of variance and Tukey’s test. Results and conclusion: The suggested formula contained 26.64% w w-1 of defatted soy flour and 0.55% w w-1 of microbial transglutaminase, which was fermented using sourdough-based mixed fermentation and provided 0.16 mg 100 g-1 of available lysine and 2.09 cm3 g-1 of specific volume. The highest lysine chemical score (22.79±0.16), essential amino acid index (35.31±0.37) and biological value (26.79±0.02) and the lowest lysine loss during the baking process seen in optimized formulation verified the effectiveness of microbial transglutaminase in lysine fortification of defatted soy flour/wheat breads (P≤0.05). Considering rheology parameters and textural analysis, microbial transglutaminase treatment increased elastic modulus and β-sheet structure. These structural changes decreased final products digestibility, which can increase using mixed fermentation based on sourdough. Conflict of interest: The authors declare no conflict of interest.